The Politics of Green Hydrogen Cooperation: Emerging Dynamics in Morocco, Algeria, and Mauritania - Weko, Silvia; Farrand, Andrew; Fakoussa, Dina; Quitzow, Rainer (2023)
Europe's growing interest in securing green hydrogen from North Africa is part of a strategic effort to enhance its energy security. The promise of green hydrogen projects in Morocco, Algeria, and Mauritania is substantial, offering economic growth and job opportunities. However, numerous factors limit these countries’ ability to develop robust local green hydrogen sectors, while political disputes—particularly around Western Sahara—complicate regional collaboration. European actors can play an important role in advancing green hydrogen’s development in the region, but must tread carefully to secure local buy-in and avoid exacerbating tensions within or between these countrie